2013
DOI: 10.1016/j.ijdevneu.2013.02.008
|View full text |Cite
|
Sign up to set email alerts
|

A circuitry and biochemical basis for tuberous sclerosis symptoms: from epilepsy to neurocognitive deficits

Abstract: Tuberous sclerosis complex (TSC) is an autosomal dominant monogenetic disorder that is characterized by the formation of benign tumors in several organs as well as brain malformations and neuronal defects. TSC is caused by inactivating mutations in one of two genes, TSC1 and TSC2, resulting in increased activity of the mammalian Target of Rapamycin (mTOR). Here, we explore the cytoarchitectural and functional CNS aberrations that may account for the neurological presentations of TSC, notably seizures, hydrocep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 163 publications
(198 reference statements)
1
65
1
Order By: Relevance
“…Indeed, the seminal paper providing translational relevance to mTOR signaling in TSC showed that the seizure phenotype in Tsc1 cKO mice was abrogated following treatment with rapamycin before the onset of seizures (Zeng et al 2008). Subsequent studies confirmed seizure relief in several mouse TSC models (for review, see Feliciano et al 2013). Three recent preclinical studies have also shown that in utero prenatal treatment with rapamycin can prevent or significantly diminish the morphological consequences of Tsc1 or Tsc2 loss in the mouse (Anderl et al 2011;Tsai et al 2012b;Way et al 2012).…”
Section: Focal Cortical Dysplasia and Tuberous Sclerosis: Paradigm Mtmentioning
confidence: 99%
“…Indeed, the seminal paper providing translational relevance to mTOR signaling in TSC showed that the seizure phenotype in Tsc1 cKO mice was abrogated following treatment with rapamycin before the onset of seizures (Zeng et al 2008). Subsequent studies confirmed seizure relief in several mouse TSC models (for review, see Feliciano et al 2013). Three recent preclinical studies have also shown that in utero prenatal treatment with rapamycin can prevent or significantly diminish the morphological consequences of Tsc1 or Tsc2 loss in the mouse (Anderl et al 2011;Tsai et al 2012b;Way et al 2012).…”
Section: Focal Cortical Dysplasia and Tuberous Sclerosis: Paradigm Mtmentioning
confidence: 99%
“…Further support on the involvement of gelsolin and dendritic spine morphology on ASD comes from a study on a neurological disorder called tuberous sclerosis complex (TSC). 30%-50% of TSC patients are affected by ASD [92][93][94][95] . The stress-induced activating transcription factor-3 (Atf3)-gelsolin cascade, following mTOR hyperactivation, was…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…One example is the recent therapeutic study on TSC patients with autistic symptoms 332 . TSC disease is caused by loss-of-function mutations in TSC1 or TSC2 genes 94,95 , which code the proteins TSC1 and TSC2. TSC1 and TSC2 bind together to form a complex that inhibits mTOR, which controls translation, proliferation, and cell growth 333 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…18 Studies with TSC1 or TSC2 knockout and knockdown mouse models have yielded important information on the role of the mTOR/TSC axis in neuronal morphology, axonogenesis, dendritic arborization, regulation of neurotransmitter-receptor expression, neuronal myelination, neuronal autophagy, cortical architecture, and astrocyte proliferation. 19,20 Table 2 provides a summary of the various transgenic mouse models that have been developed to recapitulate TSC-associated epilepsy and lists the phenotype and mTOR activation associated with each system. 19 In the context of TSC-associated epilepsy, aberrant mTOR signaling has been repeatedly demonstrated, and conditional knockout of TSC1 or TSC2 in various brain cell populations was observed to be associated with elevated levels of mTOR signaling and seizures in several different transgenic mouse models.…”
Section: Overview Of Epilepsy In Tscmentioning
confidence: 99%